Factors affecting revenue of cocoa farmers in Biru-biru District, Deli Serdang Regency, North Sumatra. (May 2019) - Pinem, N F; Rambey, R
Abstract: One of the agroforestry patterns developed in Biru-biru sub-district is the combination of Cocoa and Mindi trees. Cocoa becomes the main crop while the mindi wood becomes a shade and a hedgerow plant that can be sold for wood as a building material. The objectives of research are to know cocoa agroforestry cultivation system, the level of productivity of cocoa and the marketing channel of cocoa commodity in Biru-biru District. Data collection was done through in-depth interview, questionnaire, and Focus Group Discussion (FGD). The number of respondents to be determined in accordance with the number involved in this activity. The technique of determining the sample to be interviewed is by snowball sampling. Data analysis was done by multiple linear regression with SPSS tool. Factor affecting income are education, age, length of business, time work a day, width of land, capital, price, production, institutional farmer, and quality of cocoa. The result of the analysis shows that the factors that have a significant effect on cocoa farmer's income are capital and production. The cocoa marketing channel in Biru-biru sub-district is from farmers to collectors then directly to exporters.